2022
DOI: 10.1021/acs.jpclett.2c01169
|View full text |Cite
|
Sign up to set email alerts
|

Polaritonic Chemistry from First Principles via Embedding Radiation Reaction

Abstract: The coherent interaction of a large collection of molecules with a common photonic mode results in strong light-matter coupling, a feature that has proven highly beneficial for chemistry and has introduced the research topics polaritonic and QED chemistry. Here, we demonstrate an embedding approach to capture the collective nature while retaining the full ab initio representation of single molecules—an approach ideal for polaritonic chemistry. The accuracy of the embedding radiation-reac… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
37
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(40 citation statements)
references
References 72 publications
3
37
0
Order By: Relevance
“…radiation reaction approach) may in principle be sufficient to capture collective effects on chemical reactions at ambient conditions. 77,78 Such an approach would agree with the usual semi-classical interpretation of molecular ensembles. For a quantum-coherent "super-molecule" the question of symmetry of the total ensemble would become important.…”
Section: The Impact Of Collective Effectssupporting
confidence: 63%
“…radiation reaction approach) may in principle be sufficient to capture collective effects on chemical reactions at ambient conditions. 77,78 Such an approach would agree with the usual semi-classical interpretation of molecular ensembles. For a quantum-coherent "super-molecule" the question of symmetry of the total ensemble would become important.…”
Section: The Impact Of Collective Effectssupporting
confidence: 63%
“…Indeed, recent theoretical work suggests that collective strong coupling between a set of identical molecules and a single reacting molecule can result in stronger contribution of the reacting molecule to a polaritonic state. As a consequence, the polaritonic state can obtain a stronger local character than what we would expect from a simplified model with N identical emitters contributing with 1= ffiffiffiffi N p to the polaritonic wave function 5,44,50 . Furthermore, Coulomb mediated correlation, which we can expect to be non-negligible in solution, can result in locally enhanced dipole moments that effectively magnify the light-matter interaction strength 51 .…”
Section: Reaction Mechanism and Resonant Vibrational Strong-coupling ...mentioning
confidence: 91%
“…This preferential selection implies that the cavity has to exert sizeable effects on the single molecule within a short time-frame. Since this timescale is correlated with the light-matter coupling strength, we require also a sizeable (enhanced) light-matter coupling strength in our simulations 44 . Increasing the coupling strength further inhibits the chemical reaction (see Supplementary Fig.…”
Section: Reaction Mechanism and Resonant Vibrational Strong-coupling ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Over the past century, numerous studies have demonstrated that chemical reactions can be altered by modifying molecular structures, adding catalysts, or applying external fields. With the development of quantum mechanics, scientists have established the fundamental principles of modern chemistry, understood the underlying mechanisms of chemical reactions, and exploited quantum mechanical effects to master chemical reactions. , In general, quantum-electrodynamic (QED) effects are considered small enough to be neglected in chemical reactions, although Richard Feynman once stated that “the theory behind chemistry is quantum electrodynamics” . Recently, several experiments demonstrated that QED effects can significantly modify chemical reactions under vibrational strong coupling, , which goes beyond the scope of traditional chemistry, providing new insights into fundamental science and promoting the development of cavity chemistry (polariton chemistry). In addition, owing to the rise of cavity chemistry, cavity QED effects on transition rates, e.g., electron transfer and proton transfer, have received considerable attention. However, to achieve vibrational strong coupling, specific dielectric environments are required, such as optical cavities and plasmonic cavities, leading to the difficulty of realizing cavity-modified chemical reactions. Motivated by the recent development of cavity chemistry, we questioned whether it is possible to harness QED effects to control chemical reactions in the absence of cavities.…”
mentioning
confidence: 99%